Mouth dimorphism in scale‐eating cichlid fish from Lake Tanganyika advances individual fitness. (1st September 2018) - Indermaur, Adrian; Theis, Anya; Egger, Bernd; Salzburger, Walter
Abstract: Random asymmetry, that is the coexistence of left‐ and right‐sided (or ‐handed) individuals within a population, is a particular case of natural variation; what triggers and maintains such dimorphisms remains unknown in most cases. Here, we report a field‐based cage experiment in the scale‐eating Tanganyikan cichlid Perissodus microlepis, which occurs in two morphs in nature: left‐skewed and right‐skewed individuals with respect to mouth orientation. Using underwater cages stocked with scale‐eaters and natural prey fish, we first confirm that, under semi‐natural conditions, left‐skewed scale‐eaters preferentially attack the right flank of their prey, whereas right‐skewed individuals feed predominantly from the left side. We then demonstrate that scale‐eaters have a higher probability for successful attacks when kept in dimorphic experimental populations (left‐ and right‐skewed morphs together) as compared to monomorphic populations (left‐ or right‐skewed morphs), most likely because prey fishes fail to accustom to strikes from both sides. The significantly increased probability for attacks appears to be the selective agent responsible for the evolution and maintenance of mouth dimorphism in P. microlepis, lending further support to the hypothesis that negative frequency‐dependent selection is the stabilizing force balancing the mouth dimorphism at quasi‐equal ratios in scale‐eating cichlids.